1992
DOI: 10.1111/j.1365-2621.1992.tb08054.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcoagulation of a Whey Protein Isolate by Extrusion Cooking at Acid pH

Abstract: A whey protein isolate (WPI) was coagulated by thermomechanical processing in a twin screw extruder. Nonaggregated semi-solid spreads were obtained only in the pH range 3.5-3.9, at ca 20% protein (77% water), a barrel temperature of 90-100°C and a screw speed of lOO-200 rpm. WPI extrusion-coagulated at pH 3.9 displayed a high nitrogen solubility (NSI) (43-47%). Electrophoresis indicated that the 8-lactoglobulin constituent was entirely soluble in 1% SDS, while scanning calorimetry revealed about 82% protein un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…On the basis of the above results, the change in WP solubility during reactive SCFX under the acidic condition of pH 2.89 possibly involves the two-step processes of: (1) unfolding and exposing hydrophobic and reactive sites of molecules and (2) aggregating and increasing the molecular weight, which resulted in the loss of protein solubility. Queguiner et al (1992) produced microparticulated WPs by extruding WPI powder in the pH range of 3.5-3.9 at 77% moisture content and temperature range of 90-100°C. Their results showed that the resulting microparticulated WP product displayed high nitrogen solubility (43-47%) and it was completely soluble in the buffer containing 1% SDS.…”
Section: Protein Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the above results, the change in WP solubility during reactive SCFX under the acidic condition of pH 2.89 possibly involves the two-step processes of: (1) unfolding and exposing hydrophobic and reactive sites of molecules and (2) aggregating and increasing the molecular weight, which resulted in the loss of protein solubility. Queguiner et al (1992) produced microparticulated WPs by extruding WPI powder in the pH range of 3.5-3.9 at 77% moisture content and temperature range of 90-100°C. Their results showed that the resulting microparticulated WP product displayed high nitrogen solubility (43-47%) and it was completely soluble in the buffer containing 1% SDS.…”
Section: Protein Solubilitymentioning
confidence: 99%
“…Acidic treatments, on the other hand, showed higher protein solubility and produced non-oriented fiber arrangement of extruded proteins (Dahl and Villota, 1991;Onwulata et al, 2006). Queguiner et al (1992) also reported that the microparticulated whey protein isolate (WPI) could be obtained by extrusion at acidic pH (pH 3.9). The resulting product displayed a semi-solid, smooth texture and contained a high proportion of small particles (mean diameter $11.5 lm).…”
Section: Introductionmentioning
confidence: 96%
“…Alternative processes may be utilized instead, such as extrusion cooking at acid pH (Queguiner, Dumay, Saloucavalier, & Cheftel, 1992) or dynamic high pressure shearing, i.e., microfluidization (Dissanayake & Vasiljevic, 2009;Paquin, Lebeuf, Richard, & Kalab, 1993). The result is whey protein aggregates with particle sizes that usually range between 0.1 and 10 mm (Spiegel & Huss, 2002) and that have previously shown their ability to provide sensory sensations associated with the presence of milk fat, i.e., creaminess, when incorporated into low-fat stirred yoghurt (Janhoj, Petersen, Frost, & Ipsen, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The extrusion process has been applied to dairy ingredients to improve functional properties, replacing the traditional technique with a continuous process, and develop food products with new textural characteristics. The texturization of whey protein concentrate (WPC), whey protein isolate (WPI), and nonfat dry milk through a twin-screw extruder has been reported to develop ingredients for possible uses as fat substitutes (Queguiner, Dumay, Salou-Cavalier, & Cheftel, 1992), meat extenders (Hale, Carpenter, & Walsh, 2000;Walsh & Carpenter, 2003), high protein snacks, and protein-fortified foods (Michael & Onwulata, 2006;Walsh & Carpenter, 2003).…”
Section: Introductionmentioning
confidence: 99%